inPractice: a practical nursing package for clinical decisions - Barry Ip; Annlouise Cavanna; Beverley Corbett (Association for Learning Technology, 2005)
This paper examines the recent development of a computer-assisted learning program–in Practice– at the School of Health Science, in the University of Wales Swansea. The project, which began in 2001, was developed in close collaboration with The Meningitis Trust, the aim being to produce a software package to increase nursing students' knowledge of meningitis-related illnesses, and to enhance their decision-making and problem-solving skills by using lifelike scenarios. It incorporates two multimedia meningitis modules incorporating the use of text, film, and sound, in which students are presented with information about the illness (symptoms, treatment etc.), and are required to use their knowledge to make decisions at various key points. A general discussion of decision-making theories and CAL design principles is presented, which has provided a foundation for the main design aspects of the package. This is followed by an outline of how the program was created to promote students' application of knowledge and their decision-making and problemsolving skills. Results from an evaluation questionnaire are presented. Consideration is also given as to how the program can be extended.